MY Legalis Management System / Muhammad Hanif Nor Azman - Nor Azman, Muhammad Hanif (2017)
Dealing with legal firm requires a lot of files to be managed. Although those files are being kept nicely in a drawer, the process of retrieving those file can be quite troublesome and time consuming. The most critical part for a lawyer was deadline issue and the consequences of overlooked deadline may resulting a great loss to both lawyer and client. MY Legalis Management System was proposed to overcome these problems with the features of notification as a reminder to the lawyer. In order to develop the system, a Software Development Life Cycle (SDLC) is chosen and the selected SDLC was traditional methodology, waterfall model. This project covered only first three phases during the development which are requirement gathering and analysis, design and implementation. The system used Java programming language with eclipse as its editor and MYSQL as its database. Web notification was chosen to implement in the system. Due to the time limitation this project cover only conveyancing part and only notify user through web only. Once all the three objectives of the project achieved, the aim of the project is fulfilled and MY Legalis Management System project may help the firm to have a better management on the current business process. This project can be further enhance by expanding the scope into litigation part and email notification.